Work from Home: Lessons Learned and Implications for Post-pandemic Workspaces - McGee, Beth L.; Couillou, Ryan J.; Maalt, Kristjan (UI Scholars Hub, 2023)
The experience of working from home (WFH) has evolved due to the COVID-19 response. A concurrent mixed-methods approach was used to assess the experiences and needs of WFH during COVID-19 pandemic across eight countries. Input concerning office workspace modifications was also explored. Participants (n = 82) were from Asia, Europe, and North America. Participants were working from home more and indicated they were somewhat satisfied with WFH and saw no change in productivity. The most common experience was feeling distracted while others experienced focus or calmness. Most participants were challenged by the lack of appropriate furniture and equipment, as well as being distracted by technology and communication. Participants most frequently used dedicated workspaces and outdoor views. They preferred workspaces with natural light, neutral colours, and natural ventilation. Participants reported better thermal comfort and air quality when compared to their pre-pandemic office but less access to necessary equipment, collaboration, and communication. WFH during the pandemic challenged how people worked and shifted their experience of home interiority. The key outcomes show support for hybrid work options as well as design strategies offered for accommodating home offices in the future.